Dose–response relationship between cigarette smoking and site-specific cancer risk: protocol for a systematic review with an original design combining umbrella and traditional reviews. Issue 10 (1st November 2017) - Lugo, Alessandra; Bosetti, Cristina; Peveri, Giulia; Rota, Matteo; Bagnardi, Vincenzo; Gallus, Silvano
Abstract : Introduction: Only a limited number of meta-analyses providing risk curve functions of dose–response relationships between various smoking-related variables and cancer-specific risk are available. Methods and analysis: To identify all relevant original publications on the issue, we will conduct a series of comprehensive systematic reviews based on three subsequent literature searches: (1) an umbrella review, to identify meta-analyses, pooled analyses and systematic reviews published before 28 April 2017 on the association between cigarette smoking and the risk of 28 (namely all) malignant neoplasms; (2) for each cancer site, an updated review of original publications on the association between cigarette smoking and cancer risk, starting from the last available comprehensive review identified through the umbrella review; and (3) a review of all original articles on the association between cigarette smoking and site-specific cancer risk included in the publications identified through the umbrella review and the updated reviews. The primary outcomes of interest will be (1) the excess incidence/mortality of various cancers for smokers compared with never smokers; and (2) the dose–response curves describing the association between smoking intensity, duration and time since stopping and incidence/mortality for various cancers. For each cancer site, we will perform a meta-analysis by pooling study-specific estimates for smoking status. We will also estimate the dose–response curves for other smoking-related variables through random-effects meta-regression models based on a non-linear dose–response relationship framework. Ethics and dissemination: Ethics approval is not required for this study. Main results will be published in peer-reviewed journals and will also be included in a publicly available website. We will provide therefore the most complete and updated estimates on the association between various measures of cigarette smoking and site-specific cancer risk. This will allow us to obtain precise estimates on the cancer burden attributable to cigarette smoking. Trial registration number: This protocol was registered in the International Prospective Register of Systematic Reviews (CRD42017063991 ).